Medical Ethnobiology and Indigenous Knowledge System of the Lapcha of Fikkal VDC of Ilam, Nepal - Tamang, Pradip; Singh, Nanda B. (Journal of Institute of Science and Technology, 2015)
The main aim of this paper is to investigate the medico-ethnobiological information along with indigenous knowledge system of Lapchas, one of the endangered indigenous nationalities of Nepal from Fikkal VDC of Ilam district. They were found to have rich and profound indigenous knowledge on the use of plants and animals for various purposes. Analysis of data revealed that local Lapcha people had a rich tradition on the usage of animal species and plant species of medicinal values for medicinal use for their primary health care services. Different medicinal plant and animal species were used for the treatment of different disease/ailments. The respiratory tract infections, gastrointestinal disorders, skeleto-muscular problems and dermatological infections were the most frequent ailments/diseases treated. The findings revealed by the present study have also been supported by the works previously done on other part of the country. Journal of Institute of Science and Technology, 2014, 19(2): 45-52